The Discovery of Cyclic Lipopeptide Olenamidonins in a Deepsea-Derived Streptomyces Strain by Knocking Out a DtxR Family Regulator - Qiannan Sun; Dongqi Yu; Xueqing Zhang; Fei Xiao; Wenli Li (Marine Drugs, 2024)
Three new cyclic lipopeptides, olenamidonins A-C (1–3), in addition to two previously reported metabolites (4 and 5), were accumulated in the ΔdtxRso deletion mutant of deepsea-derived Streptomyces olivaceus SCSIO 1071. The structures of these cyclic lipopeptides were determined by a combination of spectroscopic methods and circular dichroism (CD) measurement. The antibacterial assay results showed that compounds 1–5 displayed different degrees of growth inhibition against multidrug-resistant (MDR) bacterial strains Enterococcus faecalis CCARM 5172 and Enterococcus faecium CCARM 5203 with minimum inhibitory concentrations (MICs) of 1.56−6.25 μg/mL.